factorize: D(x)=x^2-20x+100-2(10-x)(x+1). f(x)=(2x-6)(2x-1)+4-x^2. a(x)=(2x-3)(x+5)-4x^2+9. thnx...
Follow Math Help Forum on Facebook and Google+
Originally Posted by lebanon factorize: D(x)=x^2-20x+100-2(10-x)(x+1). f(x)=(2x-6)(2x-1)+4-x^2. a(x)=(2x-3)(x+5)-4x^2+9. thnx... first things first foil the brackets and collect like terms...
ya i knew.. but, d(x)=(x-10)^2-2(10-x)(x+1). and, f(x)=(2x-6)(2x-1)+(2-x)(2=x) and i didn't get a(x).
Hi $\displaystyle a(x) = (2x-3)(x+5)-4x^2+9$ $\displaystyle a(x) = (2x-3)(x+5)-(4x^2-9)$ $\displaystyle a(x) = (2x-3)(x+5)-(2x-3)(2x+3)$
View Tag Cloud